Problem associated with derelict shop houses in Kuala Lumpur / Haliza Ab. Karim - Ab. Karim, Haliza (2006)
Derelict building usually made up of abandoned buildings, although there have been cases where they are occupied, if not by their owners, then by tenants or squatters. Abandoned buildings, on the other hand, need not necessarily be in derelict condition, although in due course, the combined factors of neglect and decay would bring about the same result. Derelict buildings are not the monopoly of ghost towns and sleepy hollows. They are also found in old sections of our town and cities like Kuala Lumpur, along Jalan Petaling, nearby Masjid India and Jalan Medan Pasar, there are buildings that are not being used but have their own special character architectural value (Berita Harian, 18th Feb 2005). If too many are located in one place, it becomes the embryo for an urban ghetto. Therefore, the purpose of carried out this study is to identify abandoned shop houses in Kuala Lumpur. This research is focus on the historical background, the architectural merit and inspection of condition survey of the shop houses. It is also include the interview had been done with Kuala Lumpur City Hall about their opinion about this abandoned shop houses. On the final of this research, the suggestions are given to solve the problem of abandoned shop houses.